Cisadane Warrior’s Character Design: Re-Analyzing the Physical Cues of the Crocodile Demon Queen as a Villain - Flora, Christina; Susanto, Juan (VCD, 2025)
Character design encompasses the process of creating visually captivating and unforgettable characters for different media platforms. Derived from the user test results of the author’s previous project, designing a 360-degree 3D illustration in building an immersive virtual atmosphere of the Cisadane Warrior folktale, this research aims to reexamine the former character design of the Crocodile Demon Queen of the Cisadane Warrior folktale, transforming it into a more refined antagonist. Utilizing a brief design process, it only focuses on reassessing the visual attributes of the characters by using a literature review, a reference, and an existing study, as well as observation methods. The visual attributes include anatomy and facial features of a villain, as well as its culture identity representations. The insights gained from this study help synthesize a proper design brief and execute the character design with improvement and necessary adjustments, so that the character is visually engaging, remains cohesive, and suits better with the intended audience.